2000
DOI: 10.1530/eje.0.1430607
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of clinical symptoms in a young woman with a recurrent gonadotroph adenoma causing ovarian hyperstimulation

Abstract: Objective: To demonstrate the clinical course in a young female with gonadotroph adenoma causing ovarian stimulation. Patient and methods: Our patient was a 23-year-old woman with a history of oligomenorrhea who had previously undergone bilateral ovarian wedge resection owing to the clinical appearance of polycystic ovaries. Two years later, she sought treatment for headache, galactorrhea, history of spotting and lower abdominal distension. FSH, LH, b-LH, inhibin A and B, estradiol, prolactin (PRL), and bchori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 26 publications
1
23
1
Order By: Relevance
“…2,3 Women with intact gonadotrope adenomas and supranormal FSH levels are generally not recognized as exhibiting a syndrome, because many are over 45 years of age with ovaries devoid of pre-antral follicles, and are insensitive to the action of FSH. 4 These gonadotrope adenomas are, therefore, more difficult to diagnose in women who are perimenopausal or postmenopausal. 5 In women, gonadotropinomas should also be considered if there is a history of headaches or visual changes.…”
Section: Discussion Of Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 Women with intact gonadotrope adenomas and supranormal FSH levels are generally not recognized as exhibiting a syndrome, because many are over 45 years of age with ovaries devoid of pre-antral follicles, and are insensitive to the action of FSH. 4 These gonadotrope adenomas are, therefore, more difficult to diagnose in women who are perimenopausal or postmenopausal. 5 In women, gonadotropinomas should also be considered if there is a history of headaches or visual changes.…”
Section: Discussion Of Diagnosismentioning
confidence: 99%
“…In theory, one possible medical treatment would be the administration of a GnRH analog which would decrease FSH levels, thereby leading to resolution of OHSS; however, reports have actually shown a paradoxical increase in gonadotropin secretion in response to this treatment, 4,[15][16][17][18][19][20] and in one case OHSS was induced after initiation of GnRH therapy with dramatic increases in FSH and estradiol levels. 21 There are three reports of patients with OHSS who were initially treated medically.…”
Section: Treatment and Managementmentioning
confidence: 99%
“…Elevated α-subunit levels may indicate the presence of pituitary adenoma [8,9]. FSH secreted by the tumor cells causes the formation of the multiple ovarian cysts and may considerably increase the production of estradiol [21,22]. In some reports high estradiol levels contributed to the development of endometrial hyperplasia [17,21,23].…”
Section: Clinical Presentationmentioning
confidence: 99%
“…To determine sure nature of pituitary tumour, other pituitary hormonal assays were done -Serum ACTH -38 pg/ml (0-46), Serum cortisol -1.3 mcg/ml (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). It confirmed the nature of tumour as 'mixed pituitary adenoma' secreting FSH and prolactin.…”
Section: Case Reportmentioning
confidence: 95%
“…Women with intact gonadotrope adenomas and supra-normal FSH levels are generally not recognized as exhibiting a syndrome, because many are over 45 years of age with ovaries devoid of pre-antral follicles, and are insensitive to the action of FSH. 6 These gonadotrope adenomas are, therefore, more difficult to diagnose in women who are perimenopausal or postmenopausal. There have been few reports worldwide that have revealed that serum FSH levels were normal to slightly high in patients with combined FSH -secreting pituitary adenoma with ovarian hyperstimulation.…”
Section: Introductionmentioning
confidence: 99%